login
a(n) = |a(n-1) - a(m)| for n >= 4, where m = 2^(p+1) + 2 - n and p is the unique integer such that 2^p < n - 1 <= 2^(p+1), starting with a(1) = a(2) = a(3) = 1.
0

%I #11 Nov 08 2019 15:28:40

%S 1,1,1,0,1,1,0,1,0,1,1,0,1,1,0,1,0,1,1,0,1,1,0,1,1,0,0,1,0,0,1,0,1,1,

%T 0,0,0,1,1,1,0,1,1,0,1,1,0,1,1,0,0,1,0,0,1,0,0,1,1,0,1,1,0,1,0,1,1,0,

%U 1,1,0,1,1,1,0,0,0,1,1,1,0,1,1,0,1,1,0,1,1,0

%N a(n) = |a(n-1) - a(m)| for n >= 4, where m = 2^(p+1) + 2 - n and p is the unique integer such that 2^p < n - 1 <= 2^(p+1), starting with a(1) = a(2) = a(3) = 1.

%p a := proc(n) option remember; `if`(n < 4, 1,

%p abs(a(n - 1) - a(Bits:-Iff(n - 2$2) + 3 - n)))

%p end:

%p seq(a(n), n = 1..90); # _Petros Hadjicostas_, Nov 08 2019

%K nonn

%O 1,1

%A _Clark Kimberling_

%E Name edited by _Petros Hadjicostas_, Nov 08 2019